Impact of proximal cap ambiguity on the procedural techniques and outcomes of chronic total occlusion percutaneous coronary intervention: Insights from the PROGRESS‐CTO Registry. Issue 4 (5th February 2023) - Kostantinis, Spyridon; Simsek, Bahadir; Karacsonyi, Judit; Rempakos, Athanasios; Alaswad, Khaldoon; Megaly, Michael; Krestyaninov, Oleg; Khelimskii, Dmitrii; Karmpaliotis, Dimitrios; Jaffer, Farouc A.; Khatri, Jaikirshan J.; Poommipanit, Paul; et al.
Abstract: Background: Proximal cap ambiguity is a key parameter in the global chronic total occlusion (CTO) percutaneous coronary intervention (PCI) crossing algorithm. Methods: We examined the baseline characteristics and procedural outcomes of 9718 CTO PCIs performed in 9498 patients at 41 US and non‐US centers between 2012 and 2022. Results: Proximal cap ambiguity was present in 35% of CTO lesions. Patients whose lesions had proximal cap ambiguity were more likely to have had prior coronary artery bypass graft surgery (37% vs. 24%; p  < 0.001). Lesions with proximal cap ambiguity were more complex with higher J‐CTO score (3.1 ± 1.0 vs. 2.0 ± 1.2; p  < 0.001) and lower technical (79% vs. 90%; p  < 0.001) and procedural (77% vs. 89%; p  < 0.001) success rates compared with nonambiguous CTO lesions. The incidence of major adverse cardiovascular events (MACE) was higher in cases with proximal cap ambiguity (2.5% vs. 1.7%; p  < 0.001). The retrograde approach was more commonly used among cases with ambiguous proximal cap (50% vs. 21%; p  < 0.001) and was more likely to be the final successful crossing strategy (29% vs. 13%; p  < 0.001). The antegrade dissection and re‐entry (ADR) "move‐the‐cap" techniques were also more common among cases with proximal cap ambiguity. Conclusions: Proximal cap ambiguity in CTO lesions is associated with higher utilization of the retrograde approach and ADR, lower technical and procedural success rates, and higher incidence of in‐hospital MACE.